2004
DOI: 10.1128/jb.186.23.8058-8065.2004
|View full text |Cite
|
Sign up to set email alerts
|

Novel Roles for the AIDA Adhesin from DiarrheagenicEscherichia coli: Cell Aggregation and Biofilm Formation

Abstract: Diarrhea-causing Escherichia coli strains are responsible for numerous cases of gastrointestinal disease and constitute a serious health problem throughout the world. The ability to recognize and attach to host intestinal surfaces is an essential step in the pathogenesis of such strains. AIDA is a potent bacterial adhesin associated with some diarrheagenic E. coli strains. AIDA mediates bacterial attachment to a broad variety of human and other mammalian cells. It is a surface-displayed autotransporter protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
151
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(165 citation statements)
references
References 50 publications
8
151
1
5
Order By: Relevance
“…Most auto-aggregation studies performed thus far have found a uniform distribution of autotransporters such as Ag43 and AIDA-I (Benz & Schmidt, 1992;Henderson et al, 1997b;Owen et al, 1996;Sherlock et al, 2004). However, these studies were mainly done using laboratory E. coli K-12 strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most auto-aggregation studies performed thus far have found a uniform distribution of autotransporters such as Ag43 and AIDA-I (Benz & Schmidt, 1992;Henderson et al, 1997b;Owen et al, 1996;Sherlock et al, 2004). However, these studies were mainly done using laboratory E. coli K-12 strains.…”
Section: Discussionmentioning
confidence: 99%
“…Cell chaining in E. coli biofilm 2006; Sherlock et al, 2004Sherlock et al, , 2005. Ag43 has also recently been implicated in the long-term persistence of a uropathogenic E. coli (UPEC) strain in the urinary tract (Ulett et al, 2007), possibly during a complex intercellular lifestyle (Anderson et al, 2003;Justice et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Different specific OMPs of pathogenic E. coli strains are also involved in bacteria-eukaryotic cell adherence, bacteria-bacteria adherence and/or biofilm formation (Table 1): the plasmid-encoded Adhesin Involved in Diffuse Adherence (AIDA) of human and porcine ETEC and VTEC (Niewerth et al, 2001;Mainil et al, 2002;Sherlock et al, 2004;Bardiau et al, 2010), the chromosome or plasmid-encoded Porcine Attaching-and-effacingAssociated adhesin (Paa) of porcine EPEC and ETEC and of human O157:H7 EHEC Amezcua et al, 2002;Leclerc et al, 2007;Hernandes et al, 2009;Bardiau et al, 2010), the plasmid-encoded Shigatoxigenic Autoagglutinating Adhesin (Saa) of human and bovine VTEC (Jenkins et al, 2003;Bardiau et al, 2010), and the chromosome-encoded intimin adhesin (Int) of human and animal EPEC and EHEC (Clarke et al, 2003;Mainil, 2005a;Hernandes et al, 2009), for instance.…”
Section: Outer Membrane Proteins (Omps)mentioning
confidence: 99%
“…The AIDA-I and TibA AT proteins display approximately 25 % amino acid identity to Ag43, possess similar functional characteristics and promote cell-to-cell aggregation (Sherlock et al, 2004(Sherlock et al, , 2005. To investigate whether these proteins also impair motility in a manner similar to Ag43, we analysed MG1655 transformants containing plasmids leading to the constitutive overexpression of TibA or AIDA-I.…”
Section: Ag43-mediated Inhibition Of Motility Is Independent Of Regulmentioning
confidence: 99%
“…Ag43-mediated aggregation is a distinct phenotype that can be visualized macroscopically as flocculation and settling of cells in static liquid suspensions. The protein belongs to the AIDA group of AT proteins and exhibits a high degree of homology to several other members of the AT protein family, namely the AIDA-I adhesin involved in diffuse adherence of enteropathogenic E. coli and the TibA adhesin of enterotoxigenic E. coli (Sherlock et al, 2004(Sherlock et al, , 2005. Ag43 is cleaved into two subunits (a and b), each constituting roughly half of the protein.…”
Section: Introductionmentioning
confidence: 99%